VITAL MEDICINES NOT AVAILABLE: NATIONAL AND INTERNATIONAL REGULATION ANALYSIS, UPDATE PROPOSAL OF NATIONAL LIST - SANDOVAL, Gloria A.; VACCA G, Claudia P.; OLARTE, Jorge (Vitae, 2009)
A comparative revision was carried out on the national and international policies and regulations about access of orphan and/or vital drugs.. An analysis of: orphan drugs´ list from USA, European Union and all applications for importation of not available drugs submitted by the Drug Regulatory Authority (INVIMA) until 2006; an informal consultation with health care providers, insurance companies and distributors of vital medicines, were included, in order to improve the actual vital drugs list within the frame of public health programs. The analysis included all drugs that have been protected by Decree 2085 from 2002, as well as the imported drugs by the Ministry of Social Welfare under the public health program. 26 of 107 proposed drugs match the lists of orphan drugs from the countries analyzed and 12 are protected with exclusivity by decree 2085 from 2002.